A Novel Fluorescence-Based Screen for Inhibitors of the Initiation of DNA Replication in Bacteria - Klitgaard, Rasmus N.; Løbner-Olesen, Anders (Current Drug Discovery Technologies, 2019)
Background: One of many strategies to overcome antibiotic resistance is the discovery of compounds targeting cellular processes, which have not yet been exploited. Materials and Methods: Using various genetic tools, we constructed a novel high throughput, cellbased, fluorescence screen for inhibitors of chromosome replication initiation in bacteria. Results: The screen was validated by expression of an intra-cellular cyclic peptide interfering with the initiator protein DnaA and by over-expression of the negative initiation regulator SeqA. We also demonstrated that neither tetracycline nor ciprofloxacin triggers a false positive result. Finally, 400 extracts isolated mainly from filamentous actinomycetes were subjected to the screen. Conclusion: We concluded that the presented screen is applicable for identifying putative inhibitors of DNA replication initiation in a high throughput setup.
Keywords: fluorescence